Ukrainos visuomenės regioninė tapatybė: socialinis-humanitarinis diskursas - Vermenych, Jaroslava (Genocidas ir rezistencija, 2023)
The purpose of the article is to review the development of regional studies, to understand the strategies of geopolitical dynamics in the Ukrainian space, civilizational and cultural features of regional development, complex interdependencies between national and regional dimensions of the historical process. Attention is paid to the regional problems in Ukraine, related to the specificity of regional identities, different socio-cultural values and mental stereotypes. The application of methodological approaches of regionalism is seen as the most appropriate tool both for clarifying the conflict dimension in the formation of Ukrainian identity in the past, and for finding a constructive solution to the problem of “conflict of identities” in modern conditions. It has been proven that the scientific space of modern regional history is an acceptable field for the analysis of regional societies, the economic and demographic situation in the regions, individual and group, social and territorial identities, and local political and cultural preferences. It is emphasized that during the post-war recovery in Ukraine regional characteristics took on a role of system-forming norms and structural and functional determinants that effectively stimulate and strengthen the reconstruction processes in the regions and condition the formation of a nationwide safe spatial environment.